Analisa Pengendalian Kualitas Produk Dengan Metode Six Sigma dan Analisa Kaizen di CV. Bintang Terang Medan - Eko Prasetyo Prayogi Sihombing; Marwan Marwan (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Quality and Quality in the manufacturing industry in addition to emphasizing the products produced, it is also necessary to pay attention to the quality and quality of the production process. Thus, the final product produced is a product that is free from defects and there is no more waste that must be paid dearly because the product must be discarded or reworked. To maintain and improve the quality of the products produced, it is necessary to have quality control for the company. With quality control, it is expected that the products produced are in accordance with the standards set and deviations that occur can be immediately overcome. The Six Sigma method is a statistical concept that measures a process related to defects or defects. This method is considered as a method that is able to take a comprehensive approach, which will dramatically improve the quality of the resulting product. With the implementation of the Six Sigma method, CV. Bintang Terang Medan is expected to minimize the number of defective products to zero defects.